Evolutionary and Molecular Facts Link the WWC Protein Family to Hippo Signaling. (27th March 2014) - Wennmann, Dirk Oliver; Schmitz, Jürgen; Wehr, Michael C.; Krahn, Michael P.; Koschmal, Nora; Gromnitza, Sascha; Schulze, Ulf; Weide, Thomas; Chekuri, Anil; Skryabin, Boris V.; Gerke, Volker; Pavenstädt, Hermann; et al.
Abstract : The scaffolding protein KIBRA (also called WWC1) is involved in the regulation of important intracellular transport processes and the establishment of cell polarity. Furthermore, KIBRA/WWC1 is an upstream regulator of the Hippo signaling pathway that controls cell proliferation and organ size in animals. KIBRA/WWC1 represents only one member of the WWC protein family that also includes the highly similar proteins WWC2 and WWC3. Although the function of KIBRA/WWC1 was studied intensively in cells and animal models, the importance of WWC2 and WWC3 was not yet elucidated. Here, we describe evolutionary, molecular, and functional aspects of the WWC family. We show that the WWC genes arose in the ancestor of bilateral animals (clades such as insects and vertebrates) from a single founder gene most similar to the present KIBRA/WWC1-like sequence of Drosophila . This situation was still maintained until the common ancestor of lancelet and vertebrates. In fish, a progenitor-like sequence of mammalian KIBRA/WWC1 and WWC2 is expressed together with WWC3. Finally, in all tetrapods, the three family members, KIBRA/WWC1, WWC2, and WWC3, are found, except for a large genomic deletion including WWC3 in Mus musculus . At the molecular level, the highly conserved WWC proteins share a similar primary structure, the ability to form homo- and heterodimers and the interaction with a common set of binding proteins. Furthermore, all WWC proteins negatively regulate cell proliferation and organ growth due to a suppression of the transcriptional activity of YAP, the major effector of the Hippo pathway.